Accessibility instruments in planning practice: Bridging the implementation gap. (January 2017) - Silva, Cecília; Bertolini, Luca; te Brömmelstroet, Marco; Milakis, Dimitris; Papa, Enrica
Abstract: Accessibility concepts are increasingly acknowledged as fundamental to understand cities and urban regions. Accordingly, accessibility instruments have been recognised as valuable support tools for land-use and transport planning. However, despite the relatively large number of instruments available in the literature, they are not widely used in planning practice. This paper aims to explore why accessibility instruments are not widely used in planning practice. To this end we focus our research on perceived user-friendliness and usefulness of accessibility instruments. First, we surveyed a number of instrument developers, providing an overview on the characteristics of accessibility instruments available and on developers' perceptions of their user-friendliness in planning practice. Second, we brought together developers and planning practitioners in a number of local workshops across Europe and Australia, where participants were asked to use insights provided by accessibility instruments for the development of planning strategies. We found that most practitioners are convinced of the usefulness of accessibility instruments in planning practice, as they generate new and relevant insights for planners. Findings suggest that not only user-friendliness problems, but mainly organizational barriers and lack of institutionalization of accessibility instruments, are the main causes of the implementation gap. Thus user-friendliness improvement may provide limited contributions to the successful implementation of accessibility concepts in planning practice. In fact, there seems to be more to gain from active and continued engagement of instrument developers with planning practitioners and from the institutionalization of accessibility planning. Highlights: We investigate why accessibility instruments (AI) are not widely used in practice. Planning practitioners generally consider AIs useful. Organizational barriers and lack of formal regulatory frameworks hinder use of AIs. Improving user-friendliness may have limited contributions to implementation of AIs. Closer engagement of instrument developers with planning practitioners is needed.